The Quantified Self and the Digital Making of the Subject - Laurence Barry (The Digital Age and Its Discontents, 2020)
The Quantified Self website, created in 2008 by two Wired magazine editors, Gary Wolf and Kevin Kelly, instigated a movement for the better understanding of the self, based on numbers (Lupton 2014). The site has indeed as its slogan: ‘self-knowledge through numbers’.¹ Such a self-knowledge was promoted by the manual collection of numbers on one’s body functioning, which were analysed thanks to tools of analysis offered in the site. The founders also encouraged the construction of communities where people would share their calculation and insights with others, thus helping each other to get a better understanding of their quantified bodies.